Optic disk pit maculopathy: current management strategies - Chatziralli I (Dove Medical Press, 2018)
Irini Chatziralli, Panagiotis Theodossiadis, George P Theodossiadis 2nd Department of Ophthalmology, University of Athens, Attikon Hospital, Athens, Greece Introduction: Optic disk pit (ODP) is a rare congenital abnormality of the optic nerve head and can lead to visual impairment when macular detachment occurred. Recent advances in retinal imaging brought new insights into the pathophysiology of the disease, while new therapeutic options have been also described.Methods: We made a comprehensive search of the literature regarding the current treatment modalities for the treatment of ODP maculopathy.Results: Although there have been reported some cases of spontaneous resolution, current management of ODP maculopathy involves several surgical approaches. The most commonly used treatment alternative for ODP maculopathy management is vitrectomy, either alone or in combination with other treatment modalities, such as gas tamponade or laser photocoagulation. Other options, such as scleral buckling and inner fenestration, are also used, based on the recent findings about pathophysiology of the disease.Conclusion: The management of ODP maculopathy remains challenging. Even though there are further advances in the understanding of the disease pathophysiology, the applied treatment is not single and therapeutic modalities differ in the success rate, related to the anatomical and functional results. Keywords: optic disk pit, treatment, laser, gas tamponade, vitrectomy, scleral buckling